БУЛУТЛИ ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИБ ЎҚИТИШ МЕТОДИКАСИНИ ТАКОМИЛЛАШТИРИШ - Алламуратова, В.З. (SCIENCE and SOCIETY, 2024)
The article talks about the use of google docs services in the educational process in the general education school, which gives effective results for students and increases interest in learning, helps to develop the personality in all aspects, to think independently and to form responsibility. Recommendations are given on how the quality of education and student interest can be increased with the help of Google docs technology.
Keywords: Google docs; digital technology; computer; projector; Internet